Marātib al-Wilāyah Min al-Abdāl Wa al-Aqtāb Wa al-Nuqabā’ Wa al-Nujabā’ ‘Inda al-Muḥaddithīn - Muhammad Khoirul Mustaghfirin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2019)
This article describes the terminology of the level of the saints of Allah. in the perspectives of ḥadīth scholars. The terms above are Abdāl, Aqtāb, Nuqabā’, Nujabā’. This theme is still a debatable issue among scholars, especially scholars of ḥadīth. Therefore, the purpose of writing this article is to find out the different interpretations of experts on the traditions that talk about this issue and the status or value of the traditions (Ṣaḥīḥ, Ḥasan, Ḍa'if, or Mawḍū’). The ḥadīth on this subject is very varied in its editorial and some of its problems are caused by multiple interpretations between the Ḥadīth Experts such as Imam al-Suyūṭī, Jalāl al-Dīn 'Abd al-Raḥmān bin Abū Bakar (d. 911 H) and Imam al-Sakhāwī, Muḥammad bin 'Abd al-Raḥmān (d. 902) as well as Imam Ibn Hajar al-Asqalānī, al-Ḥāfiẓ Aḥmad bin ‘Alī bin Hajar (d. 852). They made a regarding the assessment of this ḥadīth and the understanding of its matan different explanations.